Overview of Night Promiscuity Behavior on Students Who Often Play Motorcycle Racing: Literature Review - David Rhesy Saputrodewo; Prima Dewi Kusumawati (PT. Griya Eka Sejahtera, 2021)
Background: There are so many kinds of acquaintances with teenagers and one of the most troubling in recent times is motorcycling students who have various deviant behaviors and engage in various kinds of behavior such as racing, brawls, and drinking alcohol. This is because teenagers who are members of motorcycle gangs do not only commit violations that disrupt public order, such as offenses leading to crimes that can endanger the community, such as robbery, persecution that takes the lives of others. This study aimed to explain the assistance of parents with students who often play motorcycle racing at night. Method: The method of searching for articles in several databases using certain keys in the 2015-2020 period. The results of the search found 8 journal articles that met the inclusion and exclusion criteria. Results: The habit of racing among teenagers is a form of juvenile delinquency. The teenagers involved were jockeys, spectators and mechanics. The reason for wild racing is because it is a hobby, channeling automotive talent and stress relief. The reason for racing is because it is a hobby, channeling automotive talent and stress relief. The resulting impact: disturbing the peace of the residents, damaging public facilities when an accident occurs, and the loss of self-ethics of teenagers on the road. Conclusion: There is a relationship between student social behavior and motor racing.